2010
DOI: 10.3758/cabn.10.2.270
|View full text |Cite
|
Sign up to set email alerts
|

Outcome expectancy and not accuracy determines posterror slowing: ERP support

Abstract: A considerable number of studies have recently used event-related potentials (ERPs) to investigate the mechanisms underlying error processing. Nevertheless, how these mechanisms are associated with behavioral adjustments following errors remains unclear. In the present study, we investigated how posterror slowing is linked to outcome expectations and error feedback. We used an adaptive four-choice reaction time task to manipulate outcome expectancy. Behaviorally, the results show posterror slowing when errors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
93
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(109 citation statements)
references
References 63 publications
(95 reference statements)
9
93
4
Order By: Relevance
“…However, this effect did not correlate with the amplitude of the ERN (at least when preceding error RT was not taken into account). This is in accord with the results of some studies (Gehring & Fencsik, 2001;Nunez Castellar et al, 2010;van Meel et al, 2007), but not with others (Debener et al, 2005;Gehring et al, 1993;Holroyd et al, 2005). One reason for the failure to find such a relation could be that internallycaused errors in the flanker paradigm represent a mixture of different error types (e.g., speed errors and attention errors; cf.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…However, this effect did not correlate with the amplitude of the ERN (at least when preceding error RT was not taken into account). This is in accord with the results of some studies (Gehring & Fencsik, 2001;Nunez Castellar et al, 2010;van Meel et al, 2007), but not with others (Debener et al, 2005;Gehring et al, 1993;Holroyd et al, 2005). One reason for the failure to find such a relation could be that internallycaused errors in the flanker paradigm represent a mixture of different error types (e.g., speed errors and attention errors; cf.…”
Section: Discussionsupporting
confidence: 75%
“…In the following, we consider two types of behavioral adjustments following errors. The first and most frequently reported type of behavioral adjustment is posterror slowing, reflected by generally increased response times (RTs) following errors (Laming, 1979;Rabbitt, 1966), which has been shown to be positively correlated with the Ne/ERN amplitude in some studies (Debener et al, 2005;Gehring et al, 1993;Holroyd, Yeung, Coles, & Cohen, 2005), but not in others (e.g., Gehring & Fencsik, 2001;Nunez Castellar, Kühn, Fias, & Notebaert, 2010;van Meel, Heslenfeld, Oosterlaan, & Sergeant, 2007). The second behavioral adjustment is an increase in attentional selectivity in conflict tasks, in which participants classify a target feature while ignoring a distractor feature.…”
Section: Introductionmentioning
confidence: 99%
“…One possible explanation would be that the two functions operate independently of each other. In line with this reasoning some investigators have found that the ERN and measures of post-error adaptation are not directly related (Castellar, Kühn, Fias, & Notebaert, 2010;Hajcak et al, 2003;Nieuwenhuis et al, 2001), while others found evidence to the contrary (Gehring et el., 1993). Further research will have to be conducted to shed more light on this matter in order to establish under which circumstances adaptive and regulative components of cognitive control are separate processes.…”
mentioning
confidence: 64%
“…In further support of the orienting account, PES is largest when errors are infrequent (Houtman et al, 2012;Notebaert et al, 2009). Also, postcorrect slowing is observed when correct responses are rare (Notebaert et al, 2009;Núñez Castellar, Kuhn, Fias, & Notebaert, 2010), and responses also slow after the unexpected presentation of task-irrelevant stimuli (Notebaert et al, 2009).…”
mentioning
confidence: 64%